Association of ELMO1 polymorphism with risk of Xinjiang Uygur diabetic kidney diseases - WENG Chang-ya; SONG Xue; ZHANG Hui; DUAN Ya-li; GUO Yu; LU Chen (Linchuang shenzangbing zazhi)
Objective To study whether the engulfment and cell motility 1gene(ELMO1)polymorphism is associated with a high risk of Xinjiang Uygurdiabetic kidney diseases,analyze the clinical index and biochemical index among the normal controls,simple diabetes and diabetic kidney diseases,and discuss whether the ELMO1 was independent risk factor for diabetic kidney diseases.MethodsThe allele frequency and the genotype distribution of the ELMO1rs10951509(A/G),and rs2717972(A/G)polymorphism were studied in normal controls(80cases),simple diabetes(84cases),and diabetic kidney diseases(97cases)by means of PCR sequencing technology.The Logistic regression analysis was done to detect whether the ELMO1 was an independent risk factor for diabetes kidney disease.Results Patients with diabetic kidney disease had a higher frequency of G allele of the ELMO1rs1095150 polymorphism than that of normal controls(χ~2=11.073,P<0.05)and simple diabetes(χ~2=4.078,P<0.05),but there was no significant difference in frequency of G allele between the normal controls and patients with simple diabetes(χ~2=1.758,P>0.05).Patients with diabetic kidney disease(χ~2=11.073,P<0.05)and simple diabetes(χ~2=4.078,P<0.05)had a higher frequency of G allele of the ELMO1rs2717972 polymorphism than that of normal controls(P<0.05),but there was no significant difference in frequency of G allele between the patients with diabetic kidney disease and those with simple diabetes(χ~2=1.758,P>0.05).Logistic regression analysis indicated that higher BMI,DBP,TG,and the ELMO1rs10951509 Gallele were the independent predictors for diabetic kidney disease.Conclusions The patients with ELM01rs10951509 may be more susceptible to diabetic kidney disease than diabetic patients with G allele.And the rs2717972 Gallele may be common susceptible gene to diabetic kidney disease and diabetic patients.The patients with type 2diabetes mellitus with high BMI,DBP,TG,and EMLO1rs10951509 Gallele may increase the risk of diabetic kidney disease.